Macroscopic Properties of Biomimetic Ceramics Are Governed by the Molecular Recognition at the Bioorganic–Inorganic Interface. (10th January 2018) - Kilper, Stefan; Facey, Sandra J.; Burghard, Zaklina; Hauer, Bernhard; Rothenstein, Dirk; Bill, Joachim
Abstract: Bioinspired materials design aims for high‐performing composite materials based on natural biomineralization processes and biomineral architectures. A key component to the research is the bioorganic–inorganic interface, one of the most crucial parameters for controlling the material properties. In this study, genetically engineered phages expressing an inorganic‐binding peptide for the molecular recognition of a ceramic material is exploited to generate thin film multilayer assemblies, with the phage template as minority component. The bioorganic–inorganic interface in the ceramic (zinc oxide, ZnO) multilayer systems is strengthened by the ZnO‐binding motif HSSHH of a peptide to increase Young's modulus and hardness. Applying a point‐mutated version of the peptide, DSSHH, which modulates the interface forces, shows an increased fracture toughness without deteriorating the Young's modulus and the hardness. Molecular matching of the organic phase and its modulation in order to form a specific interface is shown to be important in controlling material properties like in natural biominerals. With this tool in hand, it is not only possible to imitate the structure of biominerals but also to genetically control the molecular recognition of bioorganic molecules to induce macroscopic effects in synthetic composite materials. Abstract : Genetically engineered M13 phage templates expressing inorganic‐binding peptides enhance the mechanical performance of phage‐templated hybrid materials. The mechanical performance of the bioinspired material is modulated by the binding intensity of the phage template with the inorganic phase. The organic–inorganic interaction is thereby determined by the molecular recognition of nonbiogenic materials by the engineered phage template, which results in the macroscopic effect.